Management of glucocorticoid replacement in adrenal insufficiency shows notable heterogeneity – data from the EU‐AIR. (5th December 2016) - Murray, Robert D.; Ekman, Bertil; Uddin, Sharif; Marelli, Claudio; Quinkler, Marcus; Zelissen, Pierre M.J.; ,
Summary: Context and objective: Treatment for adrenal insufficiency (AI) remains suboptimal. Despite glucocorticoid replacement, patients with AI have reduced life expectancy and quality of life. This study aimed to describe the spectrum of management of glucocorticoid replacement in patients with AI enrolled in the European Adrenal Insufficiency Registry (EU‐AIR). Design, setting and patients: EU‐AIR is a prospective, multinational, multicentre, observational study initiated in August 2012 to monitor the long‐term safety of glucocorticoid replacement in routine clinical practice in Germany, the Netherlands, Sweden and the UK (ClinicalTrials.gov identifier: NCT01661387). This analysis included 1166 patients with primary and secondary AI (mean disease duration 16·1 ± 11·6 years) receiving long‐term glucocorticoid replacement therapy. Main outcome measure: Glucocorticoid type, dose, frequency and treatment regimen were examined. Results: Most patients (87·4%) were receiving hydrocortisone. The most common dose range, taken by 42·2% of patients, was 20 to <25 mg/day; however, 12·6% were receiving doses of ≥30 mg/day. Hydrocortisone was being taken once daily by 5·5%, twice daily by 48·7%, three times daily by 43·6% and four times daily by 2·1%. Patients with primary AI received higher replacement doses than those with secondary AI (23·4 ± 8·9 and 19·6 ± 5·9 mg/day, respectively). Twenty‐five different regimens were being used to deliver a daily hydrocortisone dose of 20 mg. Conclusions: We have shown significant heterogeneity in the type, dose, frequency and timing of glucocorticoid replacement in real‐world clinical practice. This reflects dose individualization based on patient symptoms and lifestyle in the absence of data supporting the optimal regimen.